Ketepatan Perhitungan Pajak Penghasilan Pasal 21 dan Kepatuhan Pelaporannya Atas Gaji Pegawai Tetap dan Tidak Tetap Pada PT. Tempo Inti Media Harian - Tedi Rochendi (Institut Teknologi dan Bisnis Swadharma, 2020)
Corporate Taxpayers are required to deduct the stage of Income Tax Article 21 on employees who work at that stage for other individuals, such as experts, who are paid or owed by the company. In terms of the stages of payment, including the object of Income Tax Article 21. Trend analysis is used to see the development of the PPh Article 21 PT. Tempo Inti Media Harian for the period 2016-2018. Based on the trend of certain ratio figures, you can get a picture of the increase, decrease, or constant of these ratios. Thus, company problems can be detected and can be seen with good and bad management of PPh Article 21 companies, especially at PT. Tempo Inti Media Harian for the period 2016-2018. PT. Tempo Inti Media Harian has a payroll and wage system policy that is in accordance with developments and in accordance with government policies on salaries or wages for employees. There are 2 types of stages, the following is a cut in the stages received by permanent employees every month. Income received is unbeatable with positions and grades or levels that have succeeded in reaching employees and is an object of Income Tax that will be deducted from Article 21 Income Tax, namely: (1) Regulated Income and (2) Irregular Income